Theory and simulation of amyloid aggregation process: sequence effects and defects - Ghanati, Elaheh (Kansas State University, 2016)
In this work, we present a model for the kinetics of amyloid fibril aggregation. In the model we mapped the process of Hydrogen bond (H-bond) formation and breakage to a random-walk. we captured the effect of side chains using position dependent H-bonds free energies which allows us to calculated the residence time for different binding alignments with the fibril. The residence time can be compared to the diffusion-limited attachment rate to give net aggregation stability. This stability increases exponentially with increasing number of bonds or binding energy in homopolymer chains, however for chains with patterned sequences, the residence time shows strong effects of the binding alignment. Using the residence time for uniform structures combined with estimate of the diffusion rate, we modeled and simulated the kinetics of amyloid aggregation. Results of the simulations gives the bond energies and concentrations required for the onset of growth of aggregates.
Keywords: amyloid aggregation; sequence effectsTheory simulation